Patronase Terplatform dalam Pemilu Indonesia: Grup WhatsApp, Perantara Digital, dan Mobilisasi Klientelistik - Subhan Subhan; Sastra Abijaya; Deden Faturohman (Society, 2026)
This article examines how clientelistic political practices are reorganized through digital platforms in Indonesian electoral politics. Existing studies of patronage and clientelism in Indonesia have largely emphasized face-to-face brokerage, vote-buying, local elite networks, and material exchange, while the platform-based mediation of these practices has received less systematic examination. Drawing on a qualitative interpretive case study combined with digital ethnography, this study analyses in-depth interviews with 40 informants, digital observations, social media content, and anonymized digital campaign archives collected in the context of the 2024 electoral cycle and related campaign activities. The informants consisted of campaign team members, digital volunteers, WhatsApp group administrators, political influencers or buzzers, and active social media voters. The findings show that digitalization does not replace conventional patronage but extends, reorganizes, and partly obscures it through platform-based communication networks. WhatsApp groups operate as semi-private spaces for campaign coordination, message circulation, political instruction, loyalty reinforcement, and subtle support monitoring. Digital volunteers, influencers, buzzers, and group administrators perform brokerage functions by connecting candidates with voters, amplifying narratives, managing online communities, and translating offline political exchanges into shareable digital content. Political incentives also circulate in more flexible forms, including internet quota, e-wallet transfers, operational funds, endorsement fees, content-production support, and logistical assistance for digital campaign work. These practices blur the boundaries between voluntary participation, paid promotion, campaign financing, and clientelistic mobilization. The article contributes to the literature on patronage-clientelism and digital political communication by conceptualizing platformed patronage as a hybrid electoral practice shaped by digital infrastructures, affective visibility, networked intermediation, incentive circulation, and loyalty formation.